If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 5 + -3x + -4 = 13 Reorder the terms: 5 + -4 + 5x + -3x = 13 Combine like terms: 5 + -4 = 1 1 + 5x + -3x = 13 Combine like terms: 5x + -3x = 2x 1 + 2x = 13 Solving 1 + 2x = 13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2x = 13 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = 13 + -1 2x = 13 + -1 Combine like terms: 13 + -1 = 12 2x = 12 Divide each side by '2'. x = 6 Simplifying x = 6
| n-31=20 | | -4x^2-48x-144=0 | | 4x+23x+6= | | 6.1x-9=5.1x+5 | | -2(x-14)=42 | | 7x-61=2x-1 | | (2x-4)(6x+3)=0 | | 5x+5=6x-3 | | x+5=82 | | x^2-6x+10=2x-5 | | x+6y=-27 | | -36x^2-24x-4=0 | | z+19=-7 | | x+3(x+4)= | | u+15=2+3u | | 4x-2=11x+5 | | z^2+3z-28=0 | | z+19=84 | | 5x+234=25x+7 | | -5x^2-45x-100=0 | | z/12+19=84 | | 12/0.5= | | 4(x+1)=8(2x-3) | | -1+-6x=8-9x | | (x+17)=0 | | 7x-4=2x+15 | | 3/8+9x-1/2 | | z=2/7 | | k^2+11k+28=0 | | 120.5= | | 5(x-3)(x+4)=0 | | 7y-39=3y-11 |